Kepatuhan Syariah Akad Murabahah Dalam Konsep Pembiayaan Pada Perbankan Syariah Di Indonesia - Luluk Wahyu Roficoh; Mohammad Ghozali (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2018)
Murabahah contract is a contract of financing an item by affirming the purchase price to the buyer and the buyer paying more prices as an agreed profit. Murabahah form that is carried out by Islamic bank has undergone several changes from the original. Murabahah practiced in Islamic banks is known as Murabahah li al-aamir bi al-syira. Contemporary scholars disagree about the validity of buying and selling Murabahah li al-aamir bi al-syira. The Bank carries out Murabahah with customers, at the same time representing customers so that customers can buy the items they want. Basically, the provisions relating to the Murabahah agreement have been very explicitly described in the DSN MUI Fatwa Number 04 / DSN-MUI/ IV/2000 concerning Murabahah. Thus, what has been practiced by Islamic banking in financing with the Murabahah contract has deviated several provisions in the MUI DSN Fatwa.